Significance of antigen and epitope specificity in tuberculosis - Tom H.M. Ottenhoff (Frontiers Research Topics, 2014)
Dissection of the specificity of host immune responses following infection with Mycobacterium tuberculosis is essential for designing effective vaccination and diagnostic biomarkers as well as for better understanding of immunopathogenesis of active tuberculosis. The articles in this volume of the Topics in Microbial Immunology review the significance of this area of research from both experimental models and clinical surveys. This includes T cell recognition of MHC permissive epitopes, use of algorithms for genome-based prediction of immunodominant epitopes, evaluation of candidate antigens/epitopes and adjuvants for vaccination and immunodiagnosis. Future research strategies indicate the need for better understanding of the relationship between epitope specificity and the phenotype of responding T cells and search for biomarkers with a capacity to discriminate and predict the change from latent infection to active disease. These research avenues have important potentials for improving the prevention and control of tuberculosis.